Sirtuin 2 (SIRT2): Confusing Roles in the Pathophysiology of Neurological Disorders - Chen, Xiuqi; Lu, Wenmei; Wu, Danhong (Frontiers in Neuroscience, 2021)
Sirtuin2 (SIRT2), a kind of NAD+-dependent deacetylases, is most found in the cyto-plasm and abounds in the central nervous system (CNS), which indicates its potential role in neurological diseases. Though in most cases, SIRT2 accelerates the develop-ment of neurological pathology, under certain circumstances, it protects the brain from deterioration. This review summarizes the complicated roles of SIRT2 in pa-thology and physiology of neurological diseases, compares and analyzes the diverse roles SIRT2 acts in different situations and provides possible explanations for its paradoxical functions. In the future, the rapid growth in SIRT2 research may clarify its impacts in neurological diseases, and therapeutic strategies targeting at this pro-tein may have great potentials.